2020
DOI: 10.1186/s13765-020-00527-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Lactobacillus plantarum ATCC8014 on acrylamide-induced oxidative damage in rats

Abstract: Acrylamide (AA), which is mainly found in fried foods, causes neurotoxicity, genetic toxicity, carcinogenic effects, and DNA damage. This study confirms that a strain of lactic acid bacteria (Lactobacillus plantarum ATCC8014) could alleviate the toxicity of rats by inhibiting the AA-induced oxidative damage. Forty-eight adult male SD rats were randomly divided into eight groups: control group, AA group (40 mg/kg), three different doses (1 × 10 7 CFU/ml, 1 × 10 8 CFU/ ml, 1 × 10 9 CFU/ml of Lactobacillus planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Some studies have shown that selected strains of Lactobacillus spp. can alleviate the toxicity of acrylamide against rats [21,22]. However, when the studies have looked at the detailed mechanism of this action, they have shown that it consists in removing acrylamide from the solution by its physical binding to the bacterial cell wall [23].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that selected strains of Lactobacillus spp. can alleviate the toxicity of acrylamide against rats [21,22]. However, when the studies have looked at the detailed mechanism of this action, they have shown that it consists in removing acrylamide from the solution by its physical binding to the bacterial cell wall [23].…”
Section: Introductionmentioning
confidence: 99%
“…It reacts with molecules that consist of bisulfide (SH), azanide (NH2) or hydroxide (OH). Glutathione (GSH) is a thiol that is well known for its free radical and ROS scavenging property [7,33,34] Previous research has established that rats administered with ACR have a significant decrease of GSH in brain tissue when compared to the control group [33,34,44,45]. The reduction in GSH levels results in an increase in levels of ROS that accumulates and induces oxidative stress.…”
Section: Role Of Oxidative Stress In Acrylamide Induced Neurotoxicitymentioning
confidence: 99%
“…Studies also suggest that LPO is an effect of low levels of GSH [46][47][48]. First-line defence enzymatic antioxidants like SOD, CAT and GSH-Px have reduced in ACR-treated rats [33,42,45,47]. GST is an antioxidant enzyme used to maintain the free radical balance.…”
Section: Role Of Oxidative Stress In Acrylamide Induced Neurotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that selected strains of Lactobacillus spp. can alleviate the toxicity of AA against rats [10,11]. However, when the studies have looked at the detailed mechanism of this action they have shown that it consists in removing acrylamide from the solution by its physical binding to the bacterial cell wall [12].…”
Section: Introductionmentioning
confidence: 99%